Impact of climate change on potential distribution of xero-epiphytic selaginellas (Selaginella involvens and S. repanda) in Southeast Asia - AHMAD DWI SETYAWAN; JATNA SUPRIATNA; DEDY DARNAEDI; ROKHMATULOH ROKHMATULOH; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; ILYAS NURSAMSI; WULAN RATNA KOMALA; PRAKASH PRADAN (Biodiversitas Journal of Biological Diversity, 2017)
Setyawan AD, Supriatna J, Darnaedi D, Rokhmatuloh, Sutarno, Sugiyarto, Nursamsi I, Komala WR, Pradan P. 2017. Impact of climate change on potential distribution of xero-epiphytic selaginellas (Selaginella involvens and S. repanda) in Southeast Asia. Biodiversitas 18: 1680-1695. Climate change is one of the greatest challenges for all life on earth, as it may become the dominant driver of changes in ecosystem services and biodiversity loss at the global level. Selaginella is a group of spike-mosses that seem easily affected by global warming (climate change) due to requiring water medium for fertilization. However, some species have been adapted to dry condition and may grow as epiphytes, such as S. involvens and S. repanda. Both species are commonly found in opposing a range of elevation. S. involvens is often found in high-altitude regions, whereas S. repanda is often found at lower-altitude regions. The difference in this altitudinal distributions is expected to limit redistribution mechanism of each species to adapt the climate change projections. This study model examines the potential geographic distribution of S. involvens and S. repanda under current climatic conditions and models the impact of projected climate change on their potential distribution. Future climate predictions are made with four detailed bioclimatic scenarios (i.e. RCP 2.6, RCP 4.5, RCP 6.0, and RCP 8.5) and three-time intervals (2030, 2050, 2080), which combine various climatic factors. In this modeling, it can be concluded that S. involvens and S. repanda can adapt to future climate change, and continue to be sustainable, although it is strongly influenced and shifting habitat distribution in some areas.